Construction of Character Education portrayed in Cek Toko Sebelah Movie 1 and 2: The Semiotic Studies - Yayuk Hidayah; Hastangka Hastangka (JED (Jurnal Etika Demokrasi), 2023)
The problem that is proposed in this research is about how the character education’s construction of Cek Toko Sebelah 1 and 2 movies and how the movies’ symbols convey the message to the viewers. The purpose of this research is to examine, identify, and analyze the construction of character educations in the movie of Cek Toko Sebelah 1 and 2. Specifically, the research method used in this research is qualitative. The data analysis used is semiotic data analysis. The object of this research is Cek Toko Sebelah 1 and 2 movies by Ernest Prakasa. The result of the research shows that the construction of character educations can be found through movies. In this case, Cek Toko Sebelah 1 and 2 convey the important message of character educations, they are respecting and accepting diversity as an important value as people of Indonesia. Through this research, it can be concluded that the construction of character educations in Cek Toko Sebelah 1 and 2 movies is interpreted through scenes and dialogs that contain moral messages of entrepreneurship, mutual respect, mutual understanding, resilience, and struggle for the family.